An environment-friendly process for limestone calcination with CO2 looping and recovery. (10th December 2019) - Jiang, Binfan; Xia, Dehong; Yu, Bo; Xiong, Rui; Ao, Wenqing; Zhang, Peikun; Cong, Lin
Abstract: Lime production represents the second largest contributor to industrial CO2 emission in China, but it has not been well addressed. Herein, an efficient and environment-friendly Limestone Calcination Process with CO2 Looping and Recovery (LCPCLR) is established to solve the associated environment issue. CO2 serves as heat carrier in the LCPCLR system, which provides heat for the limestone calcination. The limestone calcination occurs in pure CO2 environment, and the calcination temperature is around 900 °C when CO2 pressure ( P CO2 ) is at ∼1 atm. CaCO3 decomposition is inhibited when P CO2 exceeds the CO2 equilibrium pressure ( P CO2 eq ), and the inhibition can be solved by increase of temperature. P CO2 / P CO2 eq is suggested to be kept below 0.25 to achieve an efficient calcination process. Both higher temperature and larger gas-solid water equivalent ratio ( η g/s ) can enhance the limestone calcination. To replace the pure CO2 with CO2 /H2 O(g) mixture as the carrier gas is a promising way to enhance efficiency of the calcination process. Through the LCPCLR, more alternative fuels can be used to reduce the operating cost, and CO2 emission is reduced by around 780 kg per ton of lime manufacturing. Graphical abstract: Image 1016647 Highlights: A novel limestone calcination process with looping CO2 as heat carrier is proposed. About 780 kg CO2 can be recovered per ton of lime manufacturing. More alternative fuels can be used in the new process to reduce the operating cost. The P CO2 / P CO2 eq is suggested to be below 0.25 to achieve efficient calcination. Adding H2 O(g) into the heat carrying loop can improve the system performance.